Lysobacter profundi sp. nov., isolated from freshwater sediment and reclassification of Lysobacter panaciterrae as Luteimonas panaciterrae comb. nov. Issue 6 (8th June 2020) - Jin, Chun-Zhi; Song, Xiuli; Sung, Yun Ju; Jin, Feng-Jie; Li, Taihua; Oh, Hee-Mock; Lee, Hyung-Gwan; Jin, Long
Abstract : A polyphasic taxonomic study was carried out on strains CHu50b-3-2 T and CHu40b-3-1 isolated from a 67 cm-long sediment core collected from the Daechung Reservoir at a water depth of 17 m, Daejeon, Republic of Korea. The cells of the strains were Gram-stain-negative, non-spore-forming, non-motile and rod-shaped. Comparative 16S rRNA gene sequence studies showed a clear affiliation of two strains with γ-Proteobacteria, which showed the highest pairwise sequence similarities to Lysobacter hankyongensis KTce-2 T (96.5 %), Lysobacter pocheonensis Gsoil193 T (96.3 %), Lysobacter ginsengisoli Gsoil 357 T (96.1 %), Lysobacter solanacearum T20R-70 T (96.1 %), Lysobacter brunescens KCTC 12130 T (95.4 %) and Lysobacter capsici YC5194 T (95.3 %). The phylogenetic analysis based on 16S rRNA gene sequences showed that the strains formed a clear phylogenetic lineage with the genus Lysobacter . The major fatty acids were identified as summed feature 9 (iso-C17 : 1 ω 9 c and/or C18 : 1 10-methyl), iso-C15 : 0, iso-C16 : 0 and iso-C17 : 0 . The respiratory quinone was identified as ubiquinone Q-8. The major polar lipids were phosphatidylglycerol, diphosphatidylglycerol, phosphatidylethanolamine and an unidentified phospholipid. The genomic DNA G+C content was determined to be 66.8 mol% (genome) for strain CHu50b-3-2 T and 66.4 mol% (HPLC) for strain CHu40b-3-1. Based on the combined genotypic and phenotypic data, we propose that strains CHu50b-3-2 T and CHu40b-3-1 represent a novel species of the genus Lysobacter, for which the name Lysobacter profundi sp. nov. is proposed. The type strain is CHu50b-3-2 T (=KCTC 72973 T =CCTCC AB 2019129 T ). Besides Lysobacter panaciterrae Gsoil 068 T formed a phylogenetic group together with strain Luteimonas aquatica RIB1-20 T (EF626688) that is clearly separated from all other known Lysobacter strains. Based on the phylogenetic relationships together with fatty acid compositions, Lysobacter panaciterrae Gsoil 068 T should be reclassified as a member of the genus Luteimonas: Luteimonas aquatica comb. nov. (type strain Gsoil 068 T =KCTC 12601 T =DSM 17927 T ).